Emergency Department Drug Surveillance (EDDS) hospital's urinalysis results compared with expanded re-testing by an independent laboratory, a pilot study. (1st January 2022) - Schwartz, Brad E.; Dezman, Zachary; Billing, Amy S.; Heine, Kimberley; Massey, Ebonie; Artigiani, E. Erin; Motavalli, Mitra; Burch, Gregory; Gandhi, Priyanka; Wish, Eric D.
Abstract: Introduction: Most hospital urine toxicology screens detect a fixed, limited set of common substances. These tests are fast and accurate but may miss emerging trends in substance use in the community and clinical acumen alone is insufficient for identifying new substances. Methods: This prospective cohort study examined de-identified urine specimens obtained from patients visiting the Emergency Department (ED) at Prince George's Hospital Center (PGHC), between October 15, 2019 to November 6, 2019 and tested positive for one or more substances. The Emergency Department Drug Surveillance System (EDDS) collects quarterly exports from de-identified electronic health records (EHRs) containing urinalysis results for drug related ED visits. We performed a feasibility study of a new urine specimen submission by collecting a stratified sample of 151 urine specimens from PGHC ED patients. The specimens were tested for 240 drugs using liquid chromatography-tandem mass spectrometry (LC-MS/MS). This paper presents a comparison between the PGHC and expanded testing results. Results: The expanded urinalysis panel found more cocaine (37% vs. 20%; p < 0.01) and benzodiazepine positives (21% vs. 11%; p < 0.05) than would have been detected by the hospital screen. Additionally, the expanded toxicology panel identified fentanyl in 4–14% of the samples. Conclusion: The EHR data submitted to EDDS from the hospital urine toxicology screen correctly identified hospital substance use patterns over the approximate 1 month study period. The expanded testing also uncovered drugs that the hospital might consider adding to their routine screen. EDDS is a feasible system for monitoring and confirming recent substance use trends among ED patients Highlights: Why is this topic important? Standard hospital urine toxicology screens can miss critical changes of substance use in emergency department (ED) patients. Most urine toxicology screens used by hospitals do not detect many synthetically derived substances. What does this study attempt to show? This pilot supports the use of the Emergency Department Drug Surveillance (EDDS) database. EDDS is a centralized database to monitor substance use trends via the hospital urine toxicology ED reports. EDDS can largely identify and reflect drug use patterns amongst patient presenting to the emergency department. With EDDS clinicians caring for patients in the ED can better identify patients suffering from SUD and target interventions. What are the key findings? The expanded analysis of de-identified urine specimens accurately corroborated with EDDS. This study is unique in methodology, utilizing LC-MS/MS to confirm KIMS based urine toxicology testing from ED samples. How is patient care impacted? This pilot study supported the current urine toxicology profile being performed in the clinical research site's ED. Based on substance use trends in their clinical setting, hospitals can retain or modify their urine toxicology testing.